2015
DOI: 10.3109/15376516.2015.1061082
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and regulation of Smad7 in the TGF- β 1/Smad signaling of aristolochic acid nephropathy

Abstract: Aristolochic acid I (AAI) affects TGF-β1/Smad signaling, which causes AA nephropathy (AAN), but the mechanisms are not fully understood. We aimed to clarify whether Arkadia and UCH37 participate in TGF-β1/Smad signaling via Smad7, and the regulatory mechanisms of Smad7. One side, mice and cultured mouse renal tubular epithelial cells (RTECs) were treated with various AAI doses and concentrations, respectively; on the other side, RTECs were transfected with small interfering RNA (siRNA) expression vectors again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…39,55 In contrast, Smad7 blocks TGFb1 signaling by inhibiting Smad2/Smad3 phosphorylation and enhancing the degradation of TGFb-RI. 56,57 In this study, we observed that injury to the kidney increased expression of TGFb-RI and phosphorylation of Smad3 and decreased expression of Smad7, whereas treatment with the EZH2 inhibitor preserved Smad7 expression, which is accompanied by reduced Smad3 phosphorylation and TGFb-RI expression. These data strongly suggest that maintaining Smad7 stability is a critical mechanism by which EZH2 inhibition suppresses TGFb/Smad3 signaling.…”
Section: Discussionmentioning
confidence: 60%
“…39,55 In contrast, Smad7 blocks TGFb1 signaling by inhibiting Smad2/Smad3 phosphorylation and enhancing the degradation of TGFb-RI. 56,57 In this study, we observed that injury to the kidney increased expression of TGFb-RI and phosphorylation of Smad3 and decreased expression of Smad7, whereas treatment with the EZH2 inhibitor preserved Smad7 expression, which is accompanied by reduced Smad3 phosphorylation and TGFb-RI expression. These data strongly suggest that maintaining Smad7 stability is a critical mechanism by which EZH2 inhibition suppresses TGFb/Smad3 signaling.…”
Section: Discussionmentioning
confidence: 60%
“…4 , indomethacin led to significant repressed status of Smad7, rapid down-regulation of Smad7 consistent with its accelerated degradation. In the literature, aristolochic acid-induced nephropathy and streptozotocin-induced diabetic nephropathy were reported with significant ubiquitination of Smad7, ( 27 , 28 ) but never in NSAID-induced GI damages before our investigation. Though not investigated in the current study further, an important regulatory step involving specific ubiquitination by Smurfs (Smad-ubiquitin regulatory factors), members of the homologous to E6-associated protein C-terminus ubiquitin ligase family, mediates the proteasomal degradation of Smads and/or receptors.…”
Section: Discussionmentioning
confidence: 62%
“…33 The TGF-b1/Smad signaling pathway can control the strength and timing of downstream signals and also mediate the fibrosis of animal organs. 34 TGF-b1 can increase the expression of many fibrotic genes, including those expressing collagen extracellular matrix proteins and a-smooth muscle actin through the Smad2/3 signaling pathway. 35 Among the various regulatory factors, an increased level of TGF-b1 has the potential to stimulate bladder fibrosis.…”
Section: Discussionmentioning
confidence: 99%